Предмет: Алгебра,
автор: Настенныйдляпечати
решите пожалуйста 2, 3, 4 и 5.
Приложения:
Ответы
Автор ответа:
2
2. а) х^2-0,81=(x-0,9)*(x+0,9)
б) а^2-6a+9=(a-3)^2
3. (y+5)^2-(y-5)*(y+5=(y+5)*(y+5-(y-5))=(y+5)*(y+5-y+5)=(y+5)*10=10(y+5)=10(-4,7+5)=10*0,3=3
4. a) 4(5a-b)(5a+b)=4(25^2-b^2)=100a^2-4b^2
б) (c^4+d^3)^2=(c^4)^2++2c^2d^3+(d^3)^2=c^8+2c^4d^3+d^6
в) (x+6)^2-(x-6)^2=0
5. a)(3x-2)^2-(3x-1)(3x+1)= -2x
9x^2-12x+4-(9x^2-1)=-2x
9x^2-12x+4-9x^2+1=-2x
-12+5=-2x
-12+2x=-5
-10x=-5
x=1\2
б)25a^2-81=0
25a^2=81
a=9\5 или a=-9\5
a1=-9\5
a2=9\5
б) а^2-6a+9=(a-3)^2
3. (y+5)^2-(y-5)*(y+5=(y+5)*(y+5-(y-5))=(y+5)*(y+5-y+5)=(y+5)*10=10(y+5)=10(-4,7+5)=10*0,3=3
4. a) 4(5a-b)(5a+b)=4(25^2-b^2)=100a^2-4b^2
б) (c^4+d^3)^2=(c^4)^2++2c^2d^3+(d^3)^2=c^8+2c^4d^3+d^6
в) (x+6)^2-(x-6)^2=0
5. a)(3x-2)^2-(3x-1)(3x+1)= -2x
9x^2-12x+4-(9x^2-1)=-2x
9x^2-12x+4-9x^2+1=-2x
-12+5=-2x
-12+2x=-5
-10x=-5
x=1\2
б)25a^2-81=0
25a^2=81
a=9\5 или a=-9\5
a1=-9\5
a2=9\5
Настенныйдляпечати:
спасибо большое
Похожие вопросы
Предмет: Литература,
автор: mrfilatovd10
Предмет: Химия,
автор: simgsdvb
Предмет: Физика,
автор: mishaplay09
Предмет: Химия,
автор: VikaAfonina